The Impact of School-Parent Collaboration and Family Environment on Character Education of Students at Madrasah Ibtidaiyah - Asriana Kibtiyah; Ariga Bahrodin; Yusuf Ahmed Muaz; Khoirul Umam; Hanifuddin; Khoirotul Idawati (Universitas Islam Negeri (UIN) Salatiga, 2025)
Objectives: This study examined the influence of school–parent collaboration and family environment on the character development of madrasah ibtidaiyah students in Jombang, Indonesia. Method: Using a quantitative approach and associative descriptive method, the study involved purposive sampling of 23 units of madrasah ibtidaiyah in Jombang, Indonesia, with 47 paired respondents. The questionnaire measured three variables: School–Parent Collaboration based on Epstein’s model, Family Environment based on Baumrind’s parenting theory, and Student Character based on Lickona and Zubaedi. Data analysis included tests for normality, multicollinearity, heteroscedasticity, and multiple linear regression. Results: The results showed that school–parent collaboration had no effect on character education, family environment had no effect on character education. and school–parent collaboration and family environment together had no effect on character education, contributing only 2.4%. Theoretical Contribution: The theoretical contributions of this study are: 1) supporting Bronfenbrenner’s ecological theory, Vygotsky’s theory of the Zone of Proximal Development (ZPD), and Bandura’s social theory; 2) identifying character values in Islamic education, such as ṣidq (honesty), amānah (responsibility), ṣabr (patience), raḥmah (compassion), discipline, 'adl (justice), and solidarity; and 3) proposing character education strategies that include syirkah tarbawiyyah (education with true partnership), mas'ūliyyah musytarakah (spiritual responsibility), uswah ḥasanah (exemplary behavior), tarbiyah raqamiyyah (digital education), and tawāzun tarbawī (balanced education). Implication Future research should adopt longitudinal approaches and broader factors.